Pengaruh Learning Management System Berbasis Moodle terhadap Kemampuan Literasi Membaca Siswa Kelas V Sekolah Dasar - Aulia, Yosi; Nafiah; Syamsyul Ghufron; Mustofa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low reading literacy skills of fifth-grade elementary school students, influenced by limited reading interest, inadequate literacy activities, and the dominance of conventional teaching methods. The study aimed to determine students' reading literacy skills before and after the implementation of a Moodle-based Learning Management System (LMS) and to examine its effect on the reading literacy skills of fifth-grade elementary school students. This research employed a quantitative approach using a Pre-Experimental One-Group Pretest-Posttest Design. The sample consisted of 26 students of Class V-A of SDI Iskandar Said Surabaya, selected through purposive sampling. Data were collected using a reading literacy test developed from the AKM and PISA indicators and analyzed using descriptive statistics and the Paired Sample t-Test. The results revealed that the implementation of the Moodle-based LMS had a significant positive effect on students' reading literacy. The mean score increased from 52.65 in the pretest (categorized as "Poor") to 67.46 in the posttest (categorized as "Fair"). The Paired Sample t-Test yielded t = -10.119 with a significance value of 0.000 (p < 0.05), indicating that H0 was rejected and H1 was accepted. These findings demonstrate that the use of a Moodle-based LMS, through interactive digital materials, quizzes, and discussion forums, enhances student engagement and contributes positively to the improvement of fifth-grade students' reading literacy.